2019
DOI: 10.3390/su11041186
|View full text |Cite
|
Sign up to set email alerts
|

Features, Driving Forces and Transition of the Household Energy Consumption in China: A Review

Abstract: Household energy consumption has been a major contributor to the increase in global energy demand and carbon emission, and the household sector has also become one of the most crucial factors shaping the management of developments towards sustainability. However, there is still a knowledge gap regarding the household energy consumption in China. Due to the vast territory and the differences among regional conditions, it is critical to conduct a systemic review to illustrate the overall situation as well as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 80 publications
(104 reference statements)
0
17
0
Order By: Relevance
“…By 2030, it is estimated that about 0.5 billion people would live in China's rural areas, and the construction area of rural houses would be about 22 billion m 2 , accounting for 29% of the total construction area in the whole country [3]. A large number of rural houses and unreasonable design and construction modes would lead to the large amount of energy consumption in rural residential buildings [4][5][6][7][8]. According to statistics, the energy consumption per unit area in rural residential houses increased from 60.9 kW•h/m 2 in 2000 to 147.1 kW•h/m 2 in 2017 [9], with an average annual growth rate of about 5.3%.…”
Section: Introductionmentioning
confidence: 99%
“…By 2030, it is estimated that about 0.5 billion people would live in China's rural areas, and the construction area of rural houses would be about 22 billion m 2 , accounting for 29% of the total construction area in the whole country [3]. A large number of rural houses and unreasonable design and construction modes would lead to the large amount of energy consumption in rural residential buildings [4][5][6][7][8]. According to statistics, the energy consumption per unit area in rural residential houses increased from 60.9 kW•h/m 2 in 2000 to 147.1 kW•h/m 2 in 2017 [9], with an average annual growth rate of about 5.3%.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with other countries, China's per capita household carbon emissions are not high [13,14], but in 2012, the percentage of energy consumption caused by household consumption activities of the total consumption in China increased to 24.7% [15], which is a rising trend, especially in rural areas [16]. In China's energy reform objectives, the household sector also plays an increasingly important role [17]. Some studies calculated China's household carbon emissions from different perspectives [6,7,[18][19][20][21], including urban-rural differences and interprovincial differences.…”
Section: Introductionmentioning
confidence: 99%
“…There are many factors affecting household carbon emissions in China. Feng et al, Wiedenhofer et al, and Shi et al found that income has a large impact on residential carbon emissions [6,17,30]. Zhang et al found a positive correlation between income and household carbon emissions [4].…”
Section: Introductionmentioning
confidence: 99%
“…Evidently, if the people in a region disappear, then the household's electricity consumption will not also exist. Furthermore, some studies have recently confirmed that energy consumption presents different patterns because people in rural and urban areas have various living conditions and habits [11,12]. Thus, populations in rural and urban areas are selected as the potential driving factors of China's household electricity consumption growth.…”
Section: Driving Factor Selectionmentioning
confidence: 99%